Quasinormal modes and greybody factors of symmergent black hole - Gogoi, Dhruba Jyoti; Övgün, Ali; Demir, Durmus (Elsevier, 2023)
Symmergent gravity is an emergent gravity framework in which gravity emerges guided by gauge invariance, accompanied by new particles, and reconciled with quantum fields. In this paper, we perform a detailed study of the quasinormal modes and greybody factors of the black holes in symmergent gravity. Its relevant parameters are the quadratic curvature term cO and the vacuum energy parameter alpha. In our analyses, effects of the both parameters are investigated. Our findings suggest that, in both positive and negative direction, large |cO| values of the parameter on the quasinormal modes parallel the Schwarzschild black hole. Moreover, the quasinormal model spectrum is found to be sensitive to the symmergent parameter alpha. We contrast the asymptotic iteration and WKB methods in regard to their predictions for the quasinormal frequencies, and find that they differ (agree) slightly at small (large) multipole moments. We analyze time-domain profiles of the perturbations, and determine the greybody factor of the symmergent black hole in the WKB regime. The symmergent parameter alpha and the quadratic curvature term cO are shown to impact the greybody factors significantly. We provide also rigorous limits on greybody factors for scalar perturbations, and reaffirm the impact of model parameters.(c) 2023 Elsevier B.V. All rights reserved.
Keywords: Symmergent black hole; Gravitational waves; Quasinormal modes; Greybody factors